PEMETAAN KAPAL TERBENGKALAI BERBASIS WEB DI WILAYAH OPERASIONAL PERAIRAN PPN KARANGANTU - Virgianisa, Tania; Rosalia, Ayang Armelita; Arifin , Willdan Aprizal (UNIVERSITAS STEKOM, 2024)
The current condition of the Karangantu Archipelago Fisheries Port (PPN) is still considered unfavorable because the operational area of ​​the port waters looks dirty and shabby. There are many ships that are no longer used in the Karangantu PPN operational area. Based on the results of interviews with PPN Karangantu officers, there are several things that cause ships to be abandoned in the operational area of ​​PPN Karangantu waters, including the age of the ship, costs or capital, and human resources. Abandoned ships that are not immediately handled will result in obstacles to the flow of water traffic at the port and create a risk of collision for other ships passing by. Therefore, web-based mapping of abandoned ships (WebGIS) is needed in the operational area of ​​PPN Karangantu waters. It is hoped that the results of this abandoned ship mapping can be used by the port to report abandoned ships to the center so that they can immediately take action to transport the abandoned ships. With the existence of WebGIS mapping abandoned ships, the port does not need to go directly to the field to find the location of abandoned ships because the information can be accessed via the web that has been created. Data collection on coordinate points was carried out by field survey and tagging using the GPS Map Camera application. The research results show that there are 74 abandoned ships in the Karangantu PPN operational area.